Hepatocurative Effect of Methanol Extract of Newbouldia laevis Leaves in Alloxan-Induced Liver Damage in Albino Rats - Umaru, Isaac John; Rebecca, Tsokwa Punarimam; Tansaba, Akafa Andes; Nanmar, Chakfa; Umaru, Kerenhappuch Isaac; Ugoeze, Egeonu Stephen; Danjuma, Tyem Lawal (African Journal of Biochemistry and Molecular Biology Research, 2024)
The aim of the study is to evaluate the effect (Hepatocurative and antibacterial potential) of Newboulda laevis leaves in alloxan-induced liver damage in Wister Albino Rats. The leaves of Newbouldia laevis was bought from a local market in Wukari, Taraba State. The leaves of Newbouldia laevis was chop and then pulverized into fine powder. The methanol crude extracts andthirty-two albino Wistar rats weighing 90-220 g was used for this research. Liver toxicity was induced in male rats by an intraperitoneal single dose of 150 mg/kg body weight. samples were subjected to biochemical estimation of liver function. The result showed a significant (p≤0.05) increase in serum AST level for group II (60.6 ± 1.12) which was administered high dose of Alloxan and serves as the negative control group, when compared to the normal control group I (35.09 ± 2.07) which only received feed and water. From the result described in table 4.0 above, it showed a significant (p≤0.05) increase in ALT level for group II (58.11 ± 0.42) negative control when compared with group I (20.00 ± 0.41) normal control. Group III (29.98 ± 0.12) which received standard drug showed a significant decrease in ALT which is a sign that there is some level of repair on the liver cells. Group IV (36.22 ± 0.s70), group V (30.00 ± 0.27) and group VI (29.99 ± 0.12) which received 100, 200 and 400 mg/kg body weight of Newbouldia laevis leaves extract respectively when compared with the negative control group II, showed a significant decrease in ALT level. There was a significant (p≤0.05) increase in ALP level for group II (255.80 ± 1.12) which received Alloxan when compared with the normal control group I (80.21 ± 0.44) providing evidence to support the increase in ALT and AST level in group II, suggestive of liver injury. The treatment groups III, VI, V and VI showed significant (p<0.05) difference, when compared to the negative control group. No significant (p<0.05) difference between group V and VII. It was deduced that the total protein for group II (10.95 ± 0.37) significantly (p<0.05) decreased when compared to the normal control group I (14.13 ± 0.55). This is because low levels of total protein in the blood can occur because of impaired function of the liver. Administration of Newbouldia laevis leaves extract significantly (p<0.05) elevated total protein levels for group IV (10.99 ± 0.41), V (12.76 ± 0.41) and VI (12.98 ± 0.58). Albumin being the most abundant protein in the blood, equally followed same pattern as total protein, with Albumin level of (10.83 ± 0.10), (6.13 ± 0.05), (9.82 ± 0.18) (6.75 ± 0.13), (7.99 ± 0.10) and (9.60 ± 0.13) for group I, II, III, IV, V and V respectively. Thus, emphasizing the potential of the extract as a source agent for medication for ailment and diseases.